METHODOLOGICAL AND THEORETICAL FUNDAMENTALS OF FORMATION OF OFFICER PROFESSIONAL CULTURE AS A TOPICAL PROBLEM OF MILITARY PROFESSIONAL TRAINING (EDUCATION IN THE 21ST CENTURY, 2025)
The article substantiates the expediency of clarifying the essence of the concept of ‘professional culture of the officer’ from the standpoint of new methodological approaches: axiological, acmeological, competence-based, resource-oriented, and system-synergetic. The extended interpretation emphasizes the relevance of the issue in the modern context of military operations, taking into account the transformation of values, the technological progress of warfare, and the changing requirements for the personality and professionalism of an officer. The analysis demonstrates that the professional culture of the officer constitutes an integral professional and personal formation that combines moral, psychological, pedagogical, and technological components. These components are not isolated but mutually interdependent, forming a synergistic system that ensures effective functioning of officers in extreme conditions. A professional officer must possess an adequate axiosphere, assimilate universal and corporate values, master psychological and pedagogical tools for leadership, and demonstrate high competence in technological operations.The extended study highlights the importance of considering professional culture not merely as a set of qualities, but as a dynamic process shaped by historical, social, and cultural contexts. The war in Ukraine has intensified the need to revise the conceptual foundations of military professional training, requiring officers to be not only technically skilled but also resilient, value-driven leaders capable of maintaining morale and organizational stability.The novelty of the article lies in the integration of methodological approaches, which together offer a holistic understanding of officer professional culture as a pedagogical system. The practical significance of the study is manifested in the possibility of applying the proposed framework in the design of curricula for higher military educational institutions, in leadership training programs, and in the development of policies aimed at preventing professional deformation and ensuring career stability.Thus, the article provides a conceptual foundation for the improvement of military professional training in line with NATO standards and the demands of modern warfare. It also outlines the directions for further research, emphasizing the need to explore the technologies, methods, and principles that contribute to the sustainable formation of professional culture in military specialists.
Keywords: officer; military specialist; professional culture; competence; professionalism; pedagogical system; military professional training